La Colonia Iulia Genetiva Vrso en la literatura renacentista y barroca: un análisis historiográfico. - Salas Álvarez, Jesús (Gerión. Revista de Historia Antigua, 2001)
A series of literary works came up between the end of the 16th and the beginning of the 18th Century. In these papers Osuna was identified with the old Colonia Iulia Genetiva Vrso, the mentions made by some roman authors were also included, as well as the testimonies of the past, with the aim of reinforcing its prestige.